Engaging Students in Science Learning Through an Art-Based Approach: A Systematic Review - Bhatt, Pushp Raj (Interdisciplinary Research in Education, 2025)
The purpose of the study was to present a systematic review to explore the student's engagement, and to explain how to develop and promote conceptual understanding, equity, and transformative learning in science education through visual and performing art. For these purposes, seven articles were selected from Google Scholar, Sage Publications, Springer, Frontiers in Education, Science Education International, Institutional repositories (e.g., Scholar Works), and Scopus database which are chosen as per the basis of inclusion and exclusion criteria sets by researcher in method of systematic review approach follow the meta-analysis and meta-synthesis process. The data is analyzed in terms of theme which is generalized through systematic review of web based database includes as research articles. The systematic reviews reflect that art-based learning promotes students' engagement, conceptual understanding, develops creativity, and provides space for equity, lived experiences, and socio-cultural aspects of the learner. Likewise, the study reflect that art-based strategies promote innovation, creativity, and transform the education system. The review suggests that Art integrates STEM plays a crucial role in guiding 21st-century education, making science education more inclusive, imaginative, and transformative. Similarly, art integrated teaching incorporates the glocal knowledge in actual classroom setting that helps to develop the 4Cs skills among students. Therefore, art-based learning is milestone for science education.